1998
DOI: 10.1148/radiology.209.2.9807577
|View full text |Cite
|
Sign up to set email alerts
|

Intrathoracic multicentric Castleman disease: CT findings in 12 patients.

Abstract: Multicentric Castleman disease is characterized by the presence of systemic symptoms, bilateral hilar and mediastinal lymphadenopathy, and centrilobular nodular opacities. The pulmonary parenchymal findings are due to the associated lymphocytic interstitial pneumonitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
1
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 0 publications
4
110
1
2
Order By: Relevance
“…No radiological data were available [4]. Interstitial pneumonitis has been reported as a pulmonary feature of MCD in 12 patients [17]. However, no clinical data or HIV serological status were available in this study.…”
Section: Discussionmentioning
confidence: 89%
“…No radiological data were available [4]. Interstitial pneumonitis has been reported as a pulmonary feature of MCD in 12 patients [17]. However, no clinical data or HIV serological status were available in this study.…”
Section: Discussionmentioning
confidence: 89%
“…It was reported that calcification might be observed in 5%-10% of patients. On the other hand, multicentric lesions can typically be observed in the form of bilateral hilar and mediastinal lymphadenopathy, centrilobular nodular opacity, and rarely ground glass, consolidation, and bronchiectasis (10,12). The value of PET in diagnosis is disputed, as it is not able to distinguish between malignant disease and CD.…”
Section: Discussionmentioning
confidence: 99%
“…Hilar, mediastinal, and axillary lymphadenopathy are common, and lymphadenopathy may enhance with intravenous injection of contrast material (Fig 10) (45). Ground-glass opacities, consolidation, and bronchiectasis are less common CT findings (45). Hepatosplenomegaly, ascites, diffuse lymphadenopathy, and thickening of the retroperitoneal fascia may also occur (46).…”
Section: Multicentric Castleman Diseasementioning
confidence: 99%